Faktor Yang Mempengaruhi Kinerja Pegawai Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean B Medan - Annisa Dwi Utami; Mhd Agung Pratam Trg; M. Farhan Harahap; Annio Indah Lestari Nasution (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This research was conducted at the Customs and Excise Service Supervision and Excise Office Type B Medan Customs on Jl. Suwondo No. 1, Like Peace, Kec. Medan Polonia, Medan City, North Sumatra 20167. In this study the author uses a descriptive research method with a qualitative approach. The purpose of this paper is to determine the factors that affect the performance of employees at the Office of Supervision and Customs and Excise Services for Intermediate Types of Customs B Medan. Based on the results of research and interviews that have been carried out by the author, information is obtained regarding the factors that affect the performance of employees at the Customs and Excise Office of Intermediate Type B Customs Supervision and Service Medan, namely as follows: 1) Company Leaders; 2) Office Facilities; 3) Work Environment; 4) Job Training.